Functional Liquid Crystal Polymer Surfaces with Switchable Topographies. Issue 1 (5th November 2020) - Feng, Wei; Liu, Danqing; Broer, Dirk J.
Abstract : Surface coatings, as interfaces between functional devices and targeted objects, are critical in the performance of functional devices. Switchable topographies bring opportunities to regulate the functionality of surfaces, ranging from morphing and controllable friction to object lifting and debris removal. Various responsive materials have been investigated to develop switchable surfaces, among which liquid crystal (LC) polymers are attractive candidates due to their anisotropic properties. Herein, focus is put on recent reports of switchable surfaces made of LC polymers. The principle of actuation of LC polymer–based switchable surfaces is introduced, with following exemplary applications derived from these responsive surfaces in the field of surface morphing, switchable surface friction, and moving/lifting of objects. Finally, future possible applications of and challenges in using dynamic coatings with switchable surface topographies are discussed. Abstract : Recent progress on the development of liquid crystal polymer–based functional surfaces with switchable topographies is reviewed. The potential applications of these stimuli‐responsive surfaces in the fields of surface morphing, cleaning, and object manipulation, and future research directions are discussed.